Digitalisasi Katalog Produk: Pemberdayaan UMKM di Kecamatan Bandongan - Agus Miswanto; Fauzan Ahmad; Ridwan Saputra; Muhammad Rifqi; Krisni Rahayu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This community service is carried out in the District of Bandongan Magelang with the main objective of promoting and empowering MSMEs (UMKM) in this area. The main problem of MSMEs in this region is their low marketing capacity and their relatively limited-term capacity. Information technology instruments are needed to strengthen the network and access to digital marketing to expand marketing reach. With the UMKM Products database that the LAZIS-MU manages through the Mitra-MU application, UMKM products can be reached by the wider community.